Podocyte-related biomarkers' role in evaluating renal toxic effects of silver nanoparticles with the possible ameliorative role of resveratrol in adult male albino rats - Eman El-Sayed Khayal; Mona G. Elhadidy; Sulaiman Mohammed Alnasser; Manal Mohammad Morsy; Azza I. Farag; Samah A. El-Nagdy (Toxicology Reports)
Extensive uses of silver nanoparticles (Ag NPs) in different industries result in exposure to these nanoparticle imperatives in our daily lives. Resveratrol is found in many plants as a natural compound. The present study aimed to estimate the renal toxic effects of Ag NPs in adult male albino rats and the underlying relevant mechanisms while studying the possible role of resveratrol in ameliorating these effects. Thirty adult albino rats were split into 5 groups; control, vehicle, resveratrol (30 mg/kg), Ag NPs (300 mg/kg), and resveratrol + Ag NPs groups. The treatments were given orally for 4 weeks. Ag NPs group displayed a reduction in kidney weight ( absolute and relative), excess in urinary levels of kidney injury molecule, neutrophil gelatinase-associated lipocalin, cystatin, and blood kidney biomarkers (creatinine, urea, and potassium), increases in oxidative stress markers with the reduction in antioxidant markers, and decreases in serum sirtuin 1(SIRT1) level. Upregulation of interleukin 1 beta, tumor necrosis factor-alpha, and monocyte chemoattractant protein-1 gene expressions with downregulation of nephrin and podocin gene expressions in renal tissues were also observed. These changes were associated with histological alterations of the glomeruli and tubules, and increased area percentage of collagen fiber. A significant increase in the optical density of transforming growth factor-beta 1 and claudin-1 immunostaining was detected in the Ag NPs group when compared to other groups. All these changes were alleviated by the usage of resveratrol through its anti-oxidant, anti-inflammatory, and activation of SIRT1 recommending its use as a renoprotective agent.